INTEGRATION OF RELIGIOUS MODERATION IN ISLAMIC EDUCATION: CHALLENGES AND OPPORTUNITIES IN THE DIGITAL ERA - Hanif, Abdullah; Syarifudin, Encep; Muhtarom, Ali (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: In the face of increasing radicalism and intolerance, Islamic education in Indonesia plays a crucial role in fostering religious moderation. Purpose: This study examines the role of Islamic education in promoting religious moderation in Indonesia, focusing on the challenges and opportunities presented by the digital and globalized era. Method: Using a qualitative approach with a literature review, the study analyzes data from journals, research reports, and academic articles on religious moderation and Islamic education. Result: The findings indicate that Islamic educational institutions have successfully integrated religious moderation values into their curricula, emphasizing tolerance, non-violence, and respect for diversity. However, challenges remain, including insufficient teacher readiness, the negative influence of technology, and students' shallow understanding of religious moderation. The study suggests that improving teacher training, managing technology’s impact on education, and providing consistent institutional support are essential for strengthening religious moderation programs. Conclusion: This research contributes to understanding how digitalization and globalization affect religious moderation efforts in Islamic education and offers strategic solutions to enhance their effectiveness.